PENGARUH EDUKASI KESEHATAN TERHADAP PENGETAHUANTENTANG KEKERASAN SEKSUAL DAN KDRT - Hardilah Ayu Ramadani; Farcha Fahrica; Fitria Simatupang; Retno Dwiyan Putri; Putra Apriadi Siregar (Jurnal Inovasi Penelitian, 2022)
Sexual violence is an act or behavior that is applied with the aim of getting sexual acts or other actions and of course that leads to a person's sexuality which is carried out by force regardless of the honor and status of the relationship with the victim himself. Domestic Violence or Domestic Violence is gender-based violence that occurs in the personal realm. Based on KEMENPPPA data in 2020, there were 8,600 cases of violence against women. And the National Data on Physical and Sexual Violence against women in 2021 is 26.1. In detail, as many as 13.8 women aged 15-49 years have experienced physical violence in 2021. This study aims to prevent sexual violence and domestic violence in various perspectives, namely health, psychological and Islamic religious perspectives. The data collection instrument used a questionnaire in the form of pre-test and post-test to find out whether there was an increase in knowledge of the respondent. Factors that cause domestic violence are the husband's cheating factor, economic factors and socio-cultural factors. The data analysis that the researcher uses is univariate analysis and also bivariate analysis. And the researcher described shipiro wilk by using the normality test of the data and getting a pre test result of 0.004 < 0.05 and the researcher getting a post test result of 0.00 < 0.05 which means that the two data have an abnormal contribution, so that in terms of This is continued using the Wilcoxon test analysis with bivariate analysis.